First dorsal metacarpal artery flap with dorsal digital nerve with or without dorsal branch of the proper digital nerve produces comparable short-term sensory outcomes - Shi-Ming Feng; Jia-Ju Zhao; Filippo Migliorini; Nicola Maffulli; Wei Xu (Journal of Orthopaedic Surgery and Research, 2021)
Abstract Background The first dorsal metacarpal artery flap, including dorsal digital nerves with or without dorsal branches of the proper digital nerves, can be used to reconstruct thumb pulp defects with good results. However, it is still unclear whether there are differences in the sensory outcomes between preserving or not preserving the dorsal branches of the proper digital nerves. Methods This retrospective cohort study included 137 thumb pulp defect patients who underwent first dorsal metacarpal artery flap reconstruction procedure from October 2015 to June 2019. Patients were divided into two groups according to whether the dorsal branches of the proper digital nerves were preserved. In the non-preservation group (n = 80), the dorsal digital nerves were included in the flap for sensory reconstruction. In the preservation group (n = 57), the dorsal digital nerves and the dorsal branches of the proper digital nerves of the index finger were included in the flap. The stump of the proper digital nerves in the defect was coaptated to the donor nerves of the flap using the end-to-end fashion. At the last follow-up, static two-point discrimination, Semmes–Weinstein monofilament scores, pain, cold intolerance of the reconstructed finger, and patient satisfaction in both groups were compared. Results All patients were followed up for at least 17 months. No significant differences were found regarding pain of thumb pulp, static two-point discrimination, Semmes–Weinstein monofilament score, cold intolerance in the injured finger, and patient satisfaction. The non-preservation group presented slightly shorter operative times (p < 0.05). Conclusion There are no differences at 2 years in postoperative clinical outcomes when dorsal digital nerves are used to reconstruct flap sensation regardless of preservation of the dorsal branches of the proper digital nerves in the first dorsal metacarpal artery flap. Level of evidence: Level III, retrospective comparative study.